ANALISIS KREDIT MACET PADA PT BANK CENTRAL ASIA Tbk - -, Fitriani - (EKONOMIA, 2017)
The purpose of research is to analyze credit mace tpada Bank Central Asia Tbk from 2015 have increased or decreased if compared to the previous year of 2014. By analyzing the non-performing loans (NPL) and Loan to Funding ratio (LFR).               In accordance with the objectives of this study, then the formulation of the problem is "Non Performing Loan (NPL) and the Loan to Funding Ratio (LFR) PT Bank Central Asia Tbk in 2015 has increased or decreased compared to non-performing loans (NPLs) and Loan to Funding Ratio (LFR) in 2014? "               Basic theory used: Financial Accounting, Non Performing Loan (NPL) and the Loan to Funding Ratio (LFR). Based on the formulation of the above problems, the proposed hypothesis is as follows: "Non Performing Loan (NPL) and the Loan to Funding Ratio (LFR) PT.Bank Central Asia Tbk in 2015 increased compared to non-performing loans (NPLs) and Loan to funding ratio (LFR) in 2014. "               The analytical tool used is banking financial ratios of non-performing loans (NPLs) and Loan to Funding Ratio (LFR).            The hypothesis in this research note that Non Performing Loan (NPL) and the Loan to Funding Ratio (LFR) PT Bank Central Asia Tbk has increased, especially of non-performing loans (NPL) increased by 0.1%, ie 0.7% from the previous in 2014 amounted to 0.6%. Similarly, the Loan to Funding Ratio (LFR) also increased from the previous year in 2014, which initially amounted to 77.5% and then in 2015 to 81.9%.